2017
DOI: 10.1016/j.jjcc.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Study design for control of HEART rate in inFant and child tachyarrhythmia with heart failure Using Landiolol (HEARTFUL): A prospective, multicenter, uncontrolled clinical trial

Abstract: The study was designed and designated the "HEARTFUL study" in the hope of establishing a basis for control of HEART rate in inFant and child tachyarrhythmia Using Landiolol in children with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Landiolol has been shown to be safe and effective for the treatment of atrial arrhythmia in adults . This case showed that cardioversion did not cause suppression with stimulation of the arrhythmogenic substrates of atrial tachyarrhythmia.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Landiolol has been shown to be safe and effective for the treatment of atrial arrhythmia in adults . This case showed that cardioversion did not cause suppression with stimulation of the arrhythmogenic substrates of atrial tachyarrhythmia.…”
Section: Discussionmentioning
confidence: 76%
“…Although landiolol, an ultrashort‐acting β‐blocker, is effective for atrial tachyarrhythmia in adult patients, its efficacy in pediatric patients is unclear . Here, we report the effectiveness of landiolol for atrial tachyarrhythmia in a 2‐year‐old boy with tetralogy of Fallot and TARP syndrome.…”
Section: Introductionmentioning
confidence: 91%
“…86 Approximately 80% patients were converted to regular sinus rhythm within 24 hours after starting administration of landiolol and 90% patients had atrioventricular sequential pacing to maintain appropriate heart rate under landiolol suppression of the junctional heart rate. There is one RCT conducted by Sumitomo et al named the HEARTFUL study in which landiolol was administered to prevent tachyarrhythmia in a dose starting from 1 μg/kg/min to achieve a 20% reduction of HR in patients aged from 3 months to 15 years old patients with heart failure 87 (Table 4).…”
Section: Role Of Prophylactic Landiolol In Pediatric Patientsmentioning
confidence: 99%
“…The design of the HEARTFUL study is comprehensively described in our previous report. 26 The study was conducted in accordance with the ethical principles of the Declaration of Helsinki and Good Clinical Practice, and was approved by the Institutional Review Boards at 15 participating institutions. The study was registered in the JapicCTI database (JapicCTI-152911; http://www.japic.…”
Section: Ethicsmentioning
confidence: 99%
“…Other eligibility criteria are described in our prior report. 26 Written informed consent was obtained from all of the parents/guardians, or from the patient if considered appropriate.…”
mentioning
confidence: 99%